2016
DOI: 10.21608/scuj.2016.6663
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lentil (Lens culinaris) Coat Powder Addition on Lipid Oxidation and Quality Characteristics of Beef Burgers Stored at 4ºC

Abstract: The effects of three concentrations (1, 2 and 3%) of lentil coat powder (LCP) on physicochemical properties, lipid stability and sensory characteristics of beef burgers were investigated after 0, 3, 6, 9 and 12 days of cold storage at 4 ± 1ºC. Burgers containing LCP had lower levels of moisture, protein, fat and pH, but they had higher levels of ash, carbohydrates, total phenolic compounds (TPC), antioxidant activity and water holding capacity (WHC) when compared with the control and BHT/BHA samples. Also, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Therefore, samples with higher sums of proximate composition (protein, ash, moisture, and fiber) had lower CHO content, and vice versa. Embaby et al (2016) found a similar trend in beef burgers added with lentil coat powder.…”
Section: Proximate Composition Of Mutton Pattiesmentioning
confidence: 54%
“…Therefore, samples with higher sums of proximate composition (protein, ash, moisture, and fiber) had lower CHO content, and vice versa. Embaby et al (2016) found a similar trend in beef burgers added with lentil coat powder.…”
Section: Proximate Composition Of Mutton Pattiesmentioning
confidence: 54%